Lithuanian loanword ģērbt and its semantics in the 17th century Latvian texts - Trumpa, Anta (Baltistica, 2021)
This article describes the usage of the Lithuanian loanword ģērbt and its derivatives in the 17th century Latvian texts with the aim to find out which meanings of these words are older and which are more recent developments, and what their routes of distribution have been.The word ģērbt and its derivatives appeared in written Latvian in the 1630s with the works authored and translated by Georg Mancelius, the Baltic German clergyman living in Zemgale. In the earlier religious texts in Latvian written by clergymen living in Riga and Vidzeme, an equivalent aptērpt was used. Obviously, in Riga and Vidzeme, unlike in Zemgale, the word ģērbt was not known until it was used by G. Mancelius. As his influence on the written Latvian language grew, the usage of ģērbt and its derivatives increased rapidly. The relatively large number of derivatives possibly shows that the word had been in use in Latvian (namely, in its subdialects spoken in Zemgale) already for some time before the 17th century.In the 17th century texts, the word ģērbt and its derivatives have been assigned four main meanings – 1. ‘to create, to cultivate’, 2. ‘to dress, to clothe’, 3. ‘to decorate, to make pretty’, 4. ‘to beat’ (this meaning, most probably, was an error in the manuscript by Christoph Fürecker). The first three meanings partly coincide with those of the Lithuanian word ger͂bti, which obviously confirms the Lithuanian origin of ģērbt.The first instances of the usage of ģērbt with these meanings appear almost simultaneously, while their duration of usage has been varied. The meaning ‘to create, to cultivate’ can be found only in the 17th century texts; the meaning ‘to decorate’ was known until the beginning of the 20th century but nowadays is not used anymore, while the meaning ‘tērpt’ still dominates to this day.
Keywords: 17th century Latvian texts; Lithuanian loanwords; semantics; Georg Mancelius